Determine Mean Serum Ferritin Level in Children with Febrile Seizures and Compare with Children without Seizures - Shamsullah Bazai, Saqib Khalil, Nighat Jabeen, Mubeena Javed, Muhammad Shaheer Mannan, Ibrahim, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the mean serum ferritin level in children with febrile seizures and without febrile seizures. Study Design: Cross sectional/case control Place & Duration: Swat Medical Complex Teaching Hospital Saidu Sharif Swat/CMH Lahore from the period January 2021 to June, 2021 Methods: 140 children with ages 5 to 60 months were enrolled in this study. All the patients were equally divided into two groups. Group I consist of 70 patients with febrile seizures and group II with same patients without febrile seizures. Complete blood picture and serum ferritin level was examined and compare the findings between both groups. Data was analyzed by SPSS 24.0. Results: In group I 42 (60%) patients were male and 28 (40%) were females with mean age 24.26±10.38 months and in groupII 40 (57.14%) were males and 30 (42.86%) were females with mean age 23.65±11.56 months. Mean serum ferritin level was significantly lower in group I patients than group II 24.48±10.82ng/ml Versus 42.45±12.64ng/ml with p-value <0.05. Iron deficiency was higher in patients with febrile seizures than patients with without seizures 22 Vs 10. Conclusion: It is concluded that children with febrile seizure had significantly lower serum ferritin level and higher iron deficiency rate as compared to children without seizure.